Estrategia generadora procedimental “Genius” para el desarrollo de capacidades creativas en los estudiantes del sexto grado en el área de ciencia y ambiente de primaria de la I.E N°00536 “Manuel Segundo del Águila” - Ríos Huansi, Lisbeth (2012)
The present research was conducted in order to experience the Strategy Generating Procedural "Genius" to develop creative skills in students of Sixth Grade e in the area of Science and Environment of the primary level of El No. 00536 " Second Manuel Veiasquez Eagle "for this purpose have sought to focus the work of our expectation of research, with reference toa section of the Sixth Grade 6 having the Educationallnstitution. Research activity was initiated, with the diagnosis problem and th.e need to have children in the area of Science and Environment, which coUid be listening to the development of the . learning sessions of the course for Science and Environment, the teacher does so theoretical, expository, without the student's participation in theconstruction oftheir own knowledge and to give a twisrto this type of education traditionalist, had to design a strategic proposal. Therefore, the research was aimed to test the following hypothesis: The Strategy Generating Procedural "Geníus" will develop significantly creative abilities in students Sixth Grade "e" of the primary level of El No. 00536 "Manuel Second Eagle Velásquez in the area of Science and Environment. Rioja- 201 O. The type was applied research, experimental level, Pre design - Experiment with one group, ie, we applied the pre test and post test to the sample of 33 students. In the analysis of results is accepted the alternative hypothesis, therefore, the Strategy Generating Procedural Genius" developed significantly creative abilities in students Sixth Grade "e" of the primary level of El N°. 00536 "Manuel Second Eagle Velásquez "in the area of Science and Environment, with estimated value of less than te = -30,397 tt tabular value = 1 ,694.